الإصلاح والتفكير الاقتصادي (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
إن هذه الدراسة, تتعرض لموضوع شائك, وفي غاية الأهمية, وهو عملية الإصلاح الاقتصادي، ولكن من زاوية أحد محاوره فقط، وهو إصلاح التفكير الاقتصادي، لعلنا نساهم - ولو بجزء طفيف - في إلقاء الضوء على هذا الجانب من الموضوع الذي لم ينل حقه من الدراسة، بسبب اهتمام باحثي الإصلاح الاقتصادي بالجانب المادي المباشر فقط دون الاهتمام – بالشكل الكافي على أقل تقدير – بالجانب المعنوي, والفكري للإصلاح الاقتصادي. من هنا كان طرحنا, ومحاولة الإجابة على السؤال الكبير التالي: هل يمكن القيام بإصلاح اقتصادي دون إصلاح التفكير الاقتصادي؟ وما هي منعكسات إصلاح التفكير الاقتصادي, أو عدمه على عملية الإصلاح الاقتصادي, والتنمية المستدامة. In this study we are discussing very important and thorny object. Its process of economical reformation, only from nook of one of  its axes, is the economical bethinking reformation. We hope that to drop the light on this side of object, which not discussed enough. Because the economists are interested only with direct material side, without interested enough in moral and ideal sides. From here, we are trying to answer on following important questions: Are possible to perform economical reform before or without economical bethinking reformation? And what are the reflections of reform or not reform of economical bethinking on process of economical reformation and long development.